Komunikasi Interpersonal Antara Manajer dan Influencer Dalam Mengembangkan Konten Pada Media Sosial TikTok - Sholayubi, Rhamanda Muharry; Kusumajanti, Kusumajanti (Universitas Al Azhar Indonesia, 2025)
This study aims to explore the interpersonal communication between managers and influencers in developing content on the TikTok social media platform. Marketing strategies have transitioned through social media platforms, with influencers on social media TikTok becoming the go-to platform for companies and brands. The role of influencer marketing is huge and the fastest growing until the end of 2024. This study is expected to understanding the management of working relationships between managers and influencers. This research uses a constructivist paradigm with a qualitative approach in the form of a case study, this research explores the experiences and interactions that occur between managers and influencers. The results show that effective interpersonal communication, including aspects of openness, empathy, supportive behavior, positive behavior, and equality, plays an important role in creating and developing innovative content In addition, challenges such as differences in perception and lack of empathy were identified as barriers that can affect communication effectiveness.